Polymorphism rs10105606 of LPL as a Novel Risk Factor for Microalbuminuria - Lim ZW; Chen WL (Dove Medical Press, 2021)
Zhu Wei Lim,1 Wei Liang Chen2- 4 1Department of Obstetrics and Gynecology, Changhua Christian Hospital, Changhua, Taiwan, Republic of China; 2Division of Family Medicine, Department of Family and Community Medicine, Tri-Service General Hospital; and School of Medicine, National Defense Medical Center, Taipei, Taiwan, Republic of China; 3Division of Geriatric Medicine, Department of Family and Community Medicine, Tri-Service General Hospital; and School of Medicine, National Defense Medical Center, Taipei, Taiwan, Republic of China; 4Department of Biochemistry, National Defense Medical Center, Taipei, Taiwan, Republic of ChinaCorrespondence: Wei Liang ChenDivision of Geriatric Medicine, Department of Family Medicine, Tri-Service General Hospital, National Defense Medical Center, Number 325, Section 2, Chang-Gong Road, Nei-Hu District, Taipei, 114, Taiwan, Republic of ChinaTel +886-2-87923311 ext. 16567Fax +886-2-87927057Email weiliang0508@gmail.comIntroduction: An important clinical feature of metabolic syndrome is abdominal obesity. Microalbuminuria is important in predicting the risk of cardiovascular and renal complications in abdominal obesity patients. However, the association between microalbuminuria polymorphism and abdominal obesity has not been conducted. The objective of this study is to analyze the genetic polymorphism of microalbuminuria in participants with metabolically unhealthy obesity (MUO).Methods: Among 1325 MUO participants, we identified genomic loci underlying those with microalbuminuria, compared to those without microalbuminuria. Single nucleotide polymorphisms (SNPs) were selected with P < 1 × 10− 5 from the Manhattan plot. Multivariable linear regression and analysis of variance were used to analyze the association between different SNP genotypes and microalbuminuria.Results: The analysis showed homozygous participants for the risk allele A of rs10105606 and Affx-31885823 had 1.978-fold risk and 1.921-fold increased risk of microalbuminuria, respectively. Heterozygous distribution of rs117180252, rs10105606, and Affx-31885823 also increased the risk of microalbuminuria compared to the wild type. Further analysis showed Lipoprotein lipase (LPL), RN7SL87P, and RPL30P9 were the candidate genes associated with lipid metabolism and abdominal obesity.Conclusion: In conclusion, LPL, RN7SL87P, and RPL30P9 minor allele carriers with abdominal obesity are more susceptible to microalbuminuria, explaining the inter-individual differences of microalbuminuria in MUO patients.Keywords: metabolic syndrome, abdominal obesity, microalbuminuria, metabolically unhealthy obesity, polymorphism, lipoprotein lipase